di-Cysteine Residues of the Arabidopsis thaliana HMA4 C-Terminus Are Only Partially Required for Cadmium Transport - Ceasar, Stanislaus Antony; Lekeux, Gilles; Motte, Patrick; Xiao, Zhiguang; Galleni, Moreno; Hanikenne, Marc (Frontiers in Plant Science, 2020)
Cadmium (Cd) is highly toxic to the environment and humans. Plants are capable of absorbing Cd from the soil and of transporting part of this Cd to their shoot tissues. In Arabidopsis, the plasma membrane Heavy Metal ATPase 4 (HMA4) transporter mediates Cd xylem loading for export to shoots, in addition to zinc (Zn). A recent study showed that di-Cys motifs present in the HMA4 C-terminal extension (AtHMA4c) are essential for high affinity Zn binding and transport in planta. In this study, we have characterized the role of the AtHMA4c di-Cys motifs in Cd transport in planta and in Cd-binding in vitro. In contrast to the case for Zn, the di-Cys motifs seem to be partly dispensable for Cd transport as evidenced by limited variation in Cd accumulation in shoot tissues of hma2hma4 double mutant plants expressing native or di-Cys mutated variants of AtHMA4. Expression analysis of metal homeostasis marker genes, such as AtIRT1, excluded that maintained Cd accumulation in shoot tissues was the result of increased Cd uptake by roots. In vitro Cd-binding assays further revealed that mutating di-Cys motifs in AtHMA4c had a more limited impact on Cd-binding than it has on Zn-binding. The contributions of the AtHMA4 C-terminal domain to metal transport and binding therefore differ for Zn and Cd. Our data suggest that it is possible to identify HMA4 variants that discriminate Zn and Cd for transport.